Flash & crash days : Brazilian theater in the postdictatorship period - George, David Sanderson. (Garland reference library of the humanities ;, 2000)
"Flash and Crash Days: Brazilian Theater in the Post-Dictatorship Period examines how the absence of censorship and the exigencies of protest and ideological purity have given rise to a variety of theatrical modes. These new modes, which Brazil has never experienced in the past, allow all voices the opportunity to be heard in the marketplace of artistic ideas: women's perspectives, sexual identity, psychological issues, the individual in society, and religion.